Bioassay Testing of Infant Biscuit Supplemented with Moringa Leaf Protein Concentrate in Model of Malnutrition Rat - Kholis, Nur; Hadi, Faris; Hadi, Faris (Jurnal Teknologi Pertanian, 2010)
Malnutrition infants need high quality and quantity protein intake. So far, protein source for infant and children food product is limited in milk and its derivates which is an expensive material. Kelor (Moringa oleifera) leaf meal has been known as a potential protein source. Unfortunately, its protein digestibility is still low due to its high fiber content. The processing of Moringa Protein Concentrate (MPC) is able to eliminate its fiber content, so that it is effective to formulate in infant biscuit product as milk substitute for fighting malnutrition. The aim of this research was to determine the bioassay value of infant biscuit supplemented with MPC. The result showed that protein content of MPC was 60.48% and almost twice higher than moringa leaf meal. The protein digestibility of MPC biscuit was 80.45% and was not significantly different (P>0,05) compared to milk biscuit. Meanwhile, PER value of MPC was 2.29 and higher than milk biscuit. It concluded that MPC was effective to substitute milk in infant biscuit product and recover the health condition of malnutrition infant.Keywords: bioassay, MPC, infant biscuit, malnutrition